2020
DOI: 10.2147/idr.s251151
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inappropriate Antibiotic Use Among Inpatients Attending Madda Walabu University Goba Referral Hospital, Southeast Ethiopia: Implication for Future Use</p>

Abstract: Background: Ethiopia is one of the countries where the healthcare system is not yet developed to the required level; hence, it is not uncommon that drugs, particularly antimicrobials, are inappropriately used for infections by any causative agents, with or without prescription, in combination or not, and, of more concern, without sensitivity tests. So, it was considered important to assess the magnitude of inappropriate antimicrobial use among inpatients attending Madda Walabu University Goba Referral Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
11
1
Order By: Relevance
“…The proper use of antimicrobials will have a positive impact on reducing antimicrobial resistance development, morbidity and mortality, and improving the cost of health care. 20 The risk of emerging antibacterial resistance due to overuse and underuse of antimicrobials has often been reported to be the most worrying aspect of antibiotic treatment. 23 DTPs can result in negative patient outcomes and are associated with failure of treatment, hospital readmissions, ED visits, increased cost, increased morbidity, and increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proper use of antimicrobials will have a positive impact on reducing antimicrobial resistance development, morbidity and mortality, and improving the cost of health care. 20 The risk of emerging antibacterial resistance due to overuse and underuse of antimicrobials has often been reported to be the most worrying aspect of antibiotic treatment. 23 DTPs can result in negative patient outcomes and are associated with failure of treatment, hospital readmissions, ED visits, increased cost, increased morbidity, and increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…18 In developing countries, including Ethiopia, antimicrobials are used more frequently than any other drugs for both bacterial and non-bacterial infections. 20 However, very limited studies were done on the prevalence of antimicrobial DTPs in developing countries. To our knowledge, no previous study was done on antimicrobial DTPs among outpatients in Northeast Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…the frequent inappropriate use of antibiotics, serious adverse events, and the development of antibiotic resistance [Kemmerich et al 2006, Simoes et al 2009. Animal studies and clinical trials have confirmed the antimicrobial efficacy of biologically active substances isolated from H. helix L. [Hong et al 2015, Saleem et al 2019, Mama et al 2020, Manderson 2020.…”
Section: Introductionmentioning
confidence: 96%
“…It is important that empirical antibiotic prescription be guided by local susceptibility patterns data to reduce inappropriate antimicrobial use [13]. No data exists in Sub Saharan African countries, on the epidemiology of AMR among diabetic patients with DFU.…”
Section: Introductionmentioning
confidence: 99%